Building Brotherhood in Community Life: Implementation of Surah An-Nisa Verse 36 - Nisa, Lina Saffanatun; Nugroho, Kharis (Universitas Muhammadiyah Surakarta, 2024)
This research aims to explore the principles of life contained in Surah An-Nisa verse 36, especially in building fraternal ties as the foundation of community life. The main issue raised is how the values taught in the verse can be implemented in modern life, which is often colored by social conflicts and lack of solidarity. This verse underlines the importance of a harmonious relationship between humans and Allah (habl min Allah) and relationships between fellow humans (habl min al-nas), which are the core of life based on Islamic values. The research method used is library research which focuses on content analysis of Surah An-Nisa verse 36. This study analyzes relevant Qur'anic verses as well as the opinions of mufasirs, supported by other literature that discusses social relations and human values. The results of the study show that Surah An-Nisa verse 36 emphasizes four main principles: monotheism, kindness to parents, strengthening family relationships, and concern for vulnerable groups. The implementation of these principles can improve the quality of social relations and encourage the creation of a peaceful and prosperous society. This research is significant because it provides practical guidance for individuals and communities to build a harmonious life based on the teachings of the Qur'an, especially in the context of the challenges of modern life.